1994
DOI: 10.2323/jgam.40.271
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the surface coat and extracellular matrix of sulphidogenic biofilms enriched in sulphate-reducing bacteria involved in biocorrosion processes in the offshore oil extraction industry off Brazil's coast.

Abstract: Anaerobic sulphate-reducing bacteria (SRB) are among the most important microorganisms involved in industrial biocorrosion (7,11). Like other microorganisms, SRB attach to metal surfaces and develop firmly adherent biofilms, in which microcolonies of different bacterial species can grow, immersed in an extensive extracellular matrix (EM) of anionic polysaccharide nature (6, 7). This complex tissue-like structure influences many physiological parameters of microbial colonization, including rate of growth, nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The exopolysaccharide layer covering the biofilm creates a microenvironment that can protect bacteria from bacteriophages, antibiotics, biocides and surfactant agents (5). In another study, we observed that in SRB-enriched biofilms the morphology of the bacterial glycocalyx and of the associated extracellular matrix varied, depending on the nature of the bacterial population under study (planktonic or sessile) and on the growth medium used (9).…”
Section: Discussionmentioning
confidence: 91%
“…The exopolysaccharide layer covering the biofilm creates a microenvironment that can protect bacteria from bacteriophages, antibiotics, biocides and surfactant agents (5). In another study, we observed that in SRB-enriched biofilms the morphology of the bacterial glycocalyx and of the associated extracellular matrix varied, depending on the nature of the bacterial population under study (planktonic or sessile) and on the growth medium used (9).…”
Section: Discussionmentioning
confidence: 91%